THE APPLICATION OF DRIP IRRIGATION SYSTEM ON TOMATO (Lycopersicum esculentum Mill) - Setyaningrum, Diah Ayu (The University of Lampung, 2014)
This study aimed to analyze the performance of drip irrigation systems, determine performance of tomato treated under the irrigation systems.Field research was conducted at the Laboratory of Land and Water Resources Engineering; and at the Laboratory ofintegrated field, Faculty of Agriculture, University of Lampung in August 2013 to December 2013.Irrigation systems consisted of main componens: water supplies, Polythilene lateral tube, and emitters. Emitter on every pot, were made of Polythilene (PE) fabric.Pot experiment consisted of 32 pots, divided into two groups, a group of 16 pots was treated with surface drip irrigation system and the other half was treated with subsurface drip irrigation system. Variables observed to the irrigation systems wereflowrate, coefficient variance (CV), emition uniformity (EU). Variables observed to the plant were evapotranspiration (ETc), Kc, Soil moisture, water consumption, plant growth, and yield. The results showed that the surface drip irrigation system had flowrate of 0.96 liter/hour, CV of 0.41 and EU of 54.85%, while the subsurface drip irrigation system had flowrate of 1.08 liter/hour, CV of 0.41 and EU of 56.43%. Plants performance treated with surface drip irrigation system showed total crop evapotranspiration (ETc) of 490,8 mm, while subsurface drip irrigation system showed total crop evapotranspiration (ETc) of 580,9 mm.Higher crop evapotranspiration of subsurface drip irrigation system was due to better plant growth in the subsurface drip irrigation system. This was also shown by higher crop coefficience (Kc) of subsurface drip irrigation system.Keywords : drip irrigation, tommato, evapotranspiration, surface, sub-surface